Capacidade tecnológica e inovação em empresas de base tecnológica - Santos, Enise Aragão dos (2020)
This research aimed to identify what are the components of the technological capabilities and the teemed innovation dimensions presented in technological-based companies (TBC). Precisely, it was investigated how the TBC develops the technological capabilities to generate innovation, due to the pressure to adapt themselves to the continuous technological changes. In doing so, qualitative research was developed and the method selected was multiple case studies. The techniques adopted were semi-structured interviews with TBC top management, direct and non-participative observation, and document analysis. The results showed that in small TBC, research and development (R&D) tends to be carried out with other external partners, including 'intermediaries' or informally, as the company does not have enough capacity to internalize the entire R&D process. Besides, in the innovation processes used by managers to develop R&D, experimentation, imitation, and the inclusion of 'adoption' stand out. The five theoretical dimensions of innovation (product, process, behavioral, market, and strategy), were manifested in the studied TBC, and the most evoked by the leaders was the 'innovation in strategy', because as companies grow, they become more complex and sophisticated, requiring a more transparent and more effective corporate strategy. The technological capacity, initially represented by four components (human capital, physical capital, organizational capital and products, and services) was also identified in the interviewees' speech, and human capital was presented as the most remembered by them, due to the recognition of that employees can drive the organization to success. Finally, the theoretical and empirical research model was consolidated, with the integration of a new component of technological capacity, called 'cultural capital', which facilitates the development of innovative processes. It is believed that this thesis may provide meaningful contributions to studies on TBC, helping to identify the theoretical and empirical links that bring innovation and technological capacity together, aiming at adapting them to continuous technological changes.